THE SIGNIFICANCE OF THE TREATISE “MUSAKHKHIR AL-BILAD” IN THE RESEARCHES OF B.AHMEDOV IN THE STUDY OF THE HISTORY OF BUKHARA - S.S.Rajabov (Scholar Express Journal, 2023)
This article analyzes the issues of studying the work “Musakhkhir albilad” (“Occupation of countries”) by Muhammadyar ibn Arab Katagan by Academician Boriboy Akhmedov.Also, as a result of the analysis and insight of B. Ahmedov’s research, it was revealed that this work is of great source study significance in the study of the geographical location, political, socio-economic (1498-1610) history of Bukhara.
Keywords: Bukhara; B. Akhmedov; oriental studies; manuscript